PROFIL PEREMPUAN BEKERJA DI KLUB MALAM (STUDI KASUS PADA WAITER NEW PARAGON KTV POOL & CAFE) DI KOTA PEKANBARU - Robinson Sitompul; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The women night entertainment workers that the researchers mean in this study are adult women who work at night entertainment venues in the city of Pekanbaru, and have a range of hours ranging from 20:00 a.m.-05.00 hrs. The purpose of this study is to find out the true view of women night entertainment workers, especially as a waiter in the city of Pekanbaru. This type of research is qualitative by using a descriptive approach. The informants in this study were 3 waiters as key informants. The location of this study was in the surrounding entertainment centers in the New Paragon KTV Pool & Cafe Jalan Sultan Syarif Qasim, Rintis Village, Pekanbaru City. The reason for choosing the location is because it is one of the nightclubs of sufficient quality and has a range of areas included in Rintis Village, Pekanbaru City. and its location is in the center of the capital of Riau, so the location in this study shows that the female nightclub waiter in the New Paragon KTV Pool & Cafe. In this study we discuss the profile and daily activities and what is the background of the informants working here. In job stereotypes regarding the characteristics of social role attributes, the community tends to judge by the way they dress, hours of work, and the work environment of the female nightclub waiter.Keywords: Profile, Women workers